Pengembangan dan Pengujian Validitas Skala Perilaku Mengemudi Berbahasa Indonesia - Mulyana, Agus; Fahmi, Irfan; Azizah, Nur’aini; Natanael, Yonathan (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
In 2018, the discourse on creating a psychological test to apply for a driver's license in Indonesia was sounded, but creating the right instrument for a psychological test is not easy. In 2022 scientifically, there is one instrument for the psychological assessment process, but from a psychometric perspective, it still has many weaknesses. Therefore, this research aims to develop a psychological test that meets the elements of good validity and reliability. This study uses the factor analysis method of scale development design. The participants in this study were 323 participants from various cities in Indonesia who voluntarily participated in a series of activities obtained by purposive sampling technique. By testing the content validity with Aiken and construct validity with confirmatory factor analysis, the study found that 24 of the 30 items developed on the Driving Behavior Scale were valid and very reliable. This research implies that the Driving Behavior Scale is suitable as a psychological test for making a driver's license.